Sedimentological and Geochemical Study of Foundation Zone Sediment at Baiji City, North Iraq - LaftaS.Kadhim; Reem M. Jasim; Sabbar A. Saleh (Tikrit Journal of Pure Science)
The study includes grain size analysis, clay minerals, selected heavy metals, total dissolved solids and chemical properties. The grain size analyses of (78) samples indicate that the upper layers of the floodplain are fine where the lower layers are coarser. The identification of abundance clay minerals are; Kaolinite, Montmorilonite, Illite, Chlorite and Palygorskite. The (pH) of the sediments ranged (7.07–7.33) with average (7.22), the values of (EC) ranged (1.71-6.42) with average (3.45) and the variation may be due to the variation of climate conditions, while the sulfates SO3 between (0.256% –8.985%) with average (1.70), and that may due to presence of primary or secondary gypsum. The (T.S.S) ranged between (0.490%–12.550%) with average (3.42) and organic content range between (0.342%–3.272%) with average (1.55).